Job Crafting: A Challenge to Promote Decent Work for Vulnerable Workers - Svicher, Andrea; Di Fabio, Annamaria (Frontiers in Psychology, 2021)
In recent years, the decent work agenda has called upon vocational psychologists to advance psychological research and intervention to promote work as a human right. Furthermore, the COVID-19 pandemic is having disproportionate consequences on vulnerable workers, such as unemployment and underemployment, highlighting the need to enhance access to decent work for these workers. As a response, the present perspective article advances job crafting as a promising way to shape decent work for marginalized workers. To this end, the article deals with decent work and job crafting, starting with the definition of decent work according to the psychology of working theory (PWT) and examining the evolution of the construct of job crafting. Subsequently, the literature on job crafting is discussed, focusing on variables related to the PWT model of decent work and their effect on vulnerable workers. Finally, possibilities for further research and intervention aimed at promoting decent work through job crafting are discussed.